Analisis Sistem Jaringan Pipa Transmisi Air Baku Kecamatan Bunga Raya Kabupaten Siak - Zara Suriza; Manyuk Fauzi; Siswanto Siswanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Clean water obtained by the population of Sabak Auh up until now is still very limited. Raw water is taken from Bunga Raya and processed in Bunga Raya water treatment installation which is then the clean water is transmitted to Sabak Auh. Therefore, an alternative of transmission pipe is needed to fulfill water requirement pipe in Sabak Auh. Calculation result shows that water requirement after twenty years is 31 liters/second. Clean water transmission from Bunga Raya to Sabak Auh is 18925,1 meters in length. This research used 4 alternatives, 3 alternatives of Transmission pipe using booster pump and from the relation of discharge and head obtained, it can be conduded that the pumps used in this 4 pump alternatives are Grundfos pump with 2-pole and 4-pole. Clean water transmission system simulation for Sabak Auh is expected to be a guide for the design of transmission of PDAM Bunga Raya.Keywords: EPANET, transmission, clean water, PDAM.